The Sustainability of the Adiwiyata Program as a Means of Environmentally Caring Character Building Among Junior High School Students in Bireuen Regency - Darmuni; Rahmi Novalita; Hariki Fitrah (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This study aims to explore the sustainability of the Adiwiyata program as a character building for environmental care in public junior high school students in Bireuen district. Type of research is exploratory qualitative. The research location is UPTD of SMP Negeri 3 Makmur, Bireuen Regency. Data and research data sources were obtained through the following stages: a) observation through direct observation of the research object spontaneously towards the Adiwiyata activity program in the formation of student character, as well as a previously prepared checklist, b) Interviews with key informants, namely teachers and students of UPTD SMP Negeri 3 Makmur with informant retrieval techniques using the snowball sampling technique, c) Documentation studies obtained from field activities. Data validity techniques include; Credibility, Transferability, defendability, and confirmability. Data analysis techniques use data reduction, data display, and data interpretation, and drawing conclusions. The results of the study indicate that the UPTD of SMP Negeri 3 Makmur, Bireuen Regency, has successfully developed various effective activity programs in realizing Adiwiyata as a character building for students. These various activity programs, which include environmental-based curriculum programs, cleanliness programs, waste management programs, reforestation programs, and park programs, have contributed significantly to creating a healthy, clean, and green environment. Furthermore, the results of this study also show that the implementation of these activity programs has helped shape the character of students who care about the environment, are responsible, and have an awareness of the importance of maintaining cleanliness and environmental sustainability.